Empathy in Japanese paramedicine students: A cross‐sectional study. (16th December 2020) - Beovich, Bronwyn; Williams, Brett
Abstract: Empathy is an important characteristic for healthcare students and professionals that may improve the quality of healthcare interactions. Empathy has predominantly been studied within medicine, but also among various allied health personnel. Within paramedicine, empathy has previously been examined internationally, but not within Japan. This study used a descriptive, cross‐sectional methodology which aimed to examine self‐reported empathy in Japanese paramedic students using the Jefferson Scale of Empathy, and compare results with similar international cohorts. Empathy levels in the Japanese cohort were higher among females compared to males. In addition, there was a decrease in empathy with each subsequent year of the paramedic program, and a general decrease as age increased. This contrasts with comparable Australian cohorts which demonstrate no significant change in empathy levels during the undergraduate program. Empathy levels measured in the Japanese paramedic cohort were generally lower than for Australian cohorts. The reasons for the differences are unclear at present and thus further research in this area is required to fully determine and describe the contributing factors.